ANTI-INFLAMMATORY ACTIVITY OF AQUEOUS EXTRACT OF ALLIUM SATIUM LEAVES - Pan, Satarupa; Immidisetty, Aparna Lakshmi; Pamba, Priyanka (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aqueous extract of Allium sativum leaves (AEAL) was investigated for anti-inflammatory activity in albino rats of Wistar strain. Methods: The AEAL was screened for the presence of phytochemical constituents like terpenoids, tannins, carrageenan, flavonoids, anthraquinones, alkaloids, cardiac glycosides, etc. The anti-inflammatory activity of AEAL was evaluated by different animal models like induced paw edema and histamine-induced paw edema, using two different concentrations of AEAL namely 100 mg/kg and 200 mg/kg, respectively. Results and Conclusion: The phytochemical screening of AEAL showed the presence of carbohydrates, reducing sugars, lipids, flavonoids, ketones, alkaloids, steroids, and triterpenes. The two different concentrations of AEAL were able to inhibit the induced edema in experimental animals in a graded fashion. Keywords: Allium sativum leaves, Anti-inflammatory, Paw edema.